Hypecotumines A-D, new isoquinoline alkaloids with potential PCSK9 inhibition activity from Hypecoum erectum L. - Yinling Wei; Hongyan Wen; Lian Yang; Bodou Zhang; Xiaoyu Li; Sheng Li; Jing Dong; Zhenzhen Liang; Yu Zhang (Natural Products and Bioprospecting)
Abstract Four new isoquinoline alkaloids, hypecotumines A-D (1–4), were isolated and identified from the whole herbs of Hypecoum erectum L. Their structures were determined by a combination of HRESIMS, NMR, and X-ray diffraction analysis methods. Compounds 1–4 were characterized by a terminal double bond at C-9 and their plausible biosynthetic pathway was hypothesized. Since PCSK9 plays a key role in the development of cardiovascular disease (CVD), exploration of PCSK inhibitors from natural products are beneficial for drug discovery of CVD treatment. SPR and Western blot assays showed compound 4 had PCSK9 inhibition activity with KD value of 59.9 µM and thus elevated the LDLR level. Further molecular docking studies demonstrated that 4 and PCSK9 could form stable interactions via key hydrogen bonds. Graphical Abstract